Pemberdayaan Masyarakat dalam Pemanfaatan Kalakai (Stenochlaena palustris (Burm. F) Bedd.) sebagai Antioksidan Alami pada Kelompok Ibu-Ibu PKK di Kelurahan Palam, Kecamatan Cempaka, Banjarbaru - Ratna Restapaty; Dyera Forestryana; Hafiz Ramadhan; Revita Saputri; ‪Satrio Wibowo Rahmatullah‬; Rahmayanti Fitriah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Prevention of the spread of Covid-19 is an essential effort when there are still highly favorable rates & deaths. The provision of education to prevent the spread of Covid-19 is always carried out with community awareness-based programs to maintain immunity. Community service by utilizing kalakai as a natural antioxidant becomes one of the alternatives to support the government. Kalakai (Stenochlaena palustris (Burm. F) Bedd.)) is a nail plant that is one of the plants with antioxidants typical of Kalimantan whose history is used as traditional medicine. This potential can be utilized and applied through the empowerment of the community of Palam Village, Cempaka Subdistrict, where many Kalakai plants grow wild. The problems found include lack of information and lack of skills of citizens in food processing based on Kalakai plants, especially in terms of food processing with high antioxidants in the form of counseling to the PKK mothers group Palam Cempaka-Banjarbaru Village. The activity method is the extension of educational provision, namely the theory of antioxidants and the potential of Kalakai, and the direct demonstration/practice of making syrups, teas, and kalakai candy. Residents expect to develop processed food products into UMKM, especially of Palam village, as a business opportunity to improve people's living standards.